2005
DOI: 10.1093/brain/awh558
|View full text |Cite
|
Sign up to set email alerts
|

Altered motor nerve excitability in end-stage kidney disease

Abstract: Although multiple toxins have been implicated in the development of uraemic neuropathy, no causative agent has been identified. In the present study, the excitability properties of lower limb motor nerves in patients with end-stage kidney disease treated with haemodialysis were measured before, during and after a standard 5 h haemodialysis session, in an attempt to explore the pathophysiology of uraemic neuropathy. Compound muscle action potentials were recorded from tibialis anterior and extensor digitorum br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
109
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 54 publications
12
109
0
6
Order By: Relevance
“…Multiple excitability parameters were recorded using previously published protocols (10,14,15). These parameters included threshold electrotonus and current threshold recordings which utilize subthreshold electrical stimuli to provide information on nerve membrane potential and internodal conductances (16).…”
Section: Nerve Excitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple excitability parameters were recorded using previously published protocols (10,14,15). These parameters included threshold electrotonus and current threshold recordings which utilize subthreshold electrical stimuli to provide information on nerve membrane potential and internodal conductances (16).…”
Section: Nerve Excitabilitymentioning
confidence: 99%
“…These insights were provided through the use of novel nerve excitability techniques, a clinical method that enables indirect assessment of ion channels, pumps and exchangers that are involved in the process of nerve impulse conduction (8). These techniques have proven particularly useful in detecting changes in peripheral nerve function in patients with chronic kidney disease (CKD), with previous studies demonstrating prominent changes in CKD patients receiving renal replacement therapies (9,10), changes that are undetectable using routine nerve conduction studies (11). The present study was undertaken to investigate the mechanisms underlying neurotoxicity in patients receiving immunosuppressive treatment following renal transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral Neuropathy -is diagnosed (10) • When the patient complained of at least one of the followings in his extremities: Numbness, pain or burning sensation…”
Section: Valsalva Maneuvermentioning
confidence: 99%
“…(10) Mononeuropathy: is diagnosed when the patient complained of pain and/or numbness and there is impaired pinprick, light touch and/or reflexes in dermatomal distribution of a single nerve. (10) Cranial Neuropathy: is considered (10) when one of the following is present:…”
Section: Mustafa Rasool Hussein Hasanain Mohammed Ali Makki and Wasanmmentioning
confidence: 99%
“…Studies of neuropathy in ESKD have demonstrated prevalence rates which vary from 60 to 100%, depending on the choice of nerve segments, the indices measured and the number of nerves studied [10][11][12][13][14][15][16][17][18][19][20][21] .…”
Section: Incidence and Clinical Features Of Neuropathy In Crfmentioning
confidence: 99%